PENGARUH SOCIAL COMMERCE FEATURES TIKTOK SHOP TERHADAP IMPULSIVE BUYING DENGAN HEDONIC MOTIVATION SEBAGAI VARIABEL MODERASI PADA MAHASISWA PENDIDIKAN EKONOMI UNIVERSITAS NEGERI SURABAYA - Aldora Intania Wulansari; Retno Mustika Dewi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to examine the effect of Social Commerce Features on Impulsive Buying with Hedonic Motivation as a moderating variable among students of the Economics Education Study Program, Universitas Negeri Surabaya, who use TikTok Shop. This research employed a quantitative approach using a survey method. Data were collected through an online questionnaire distributed to 75 respondents selected using purposive sampling. The data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS 4. The results indicate that Social Commerce Features have a positive and significant effect on Impulsive Buying. Furthermore, Hedonic Motivation significantly moderates the relationship between Social Commerce Features and Impulsive Buying with a negative moderating effect, indicating that higher hedonic motivation weakens the influence of Social Commerce Features on impulsive buying behavior. The structural model demonstrates good explanatory and predictive capabilities, supported by an R² value of 0.737, Q² value of 0.669, and SRMR value of 0.072. Overall, the findings suggest that Social Commerce Features encourage impulsive buying, while Hedonic Motivation alters consumers' responses to social commerce stimuli on TikTok Shop.